Urban trees appraisal, comparison of formulas - Ponce-Donoso, Mauricio; Vallejos-Barra, Óscar (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
The practice of monetary valuation of urban trees conducted in urban settings is usually done through formulas.The aim of the study was to compare the monetary results from the application of 12 formulas, 2 Chilean and 10 from other countries, carried out by four junior appraisers. 30 trees were assessed in three different districts of Chile, Santiago, Talca and Concepción, producing 1.440 data. The results were analyzed using Kruskal-Wallis non-parametric test for variance and Fisher’s least significant difference (LSD) multiple comparison.The highest values were obtained with STEM, Helliwell and Burnley, average values were obtained with Tedesco, N. Granada, COPIMA and Italian M., and lower values with Peñalolén M., Swiss M., CTLA, French M. and Danish M.Significant difference between valuations methods were found, while no significant differences between appraisers were found. The basic value and the composition of the formula showed a high impact on the final outcome of the assessment. The use of non-parametric statistical test extends the formulas analysis.